Математическая модель процесса идентификации конфигурации проекта в турбулентном окружении - Рудницкий, С. И. (НТУ "ХПИ", 2015)
В статье получила развитие ранее разработанная математическая модель процесса идентификации конфигурации проекта путем учета фактора турбулентности проектного окружения, для чего был применен метод динамического программирования. Сделан вывод о практической применимости этой модели для стабильных по своей конфигурации проектов.

In the article the previously developed mathematical model of the project configuration identification process was further developed by taking into account the factor of turbulent environment. It was done by applying the method of dynamic programming. It was concluded that this model is suitable for projects with the stable configuration.
Mathematical model of the project configuration identification process in turbulent environment
Keywords: управление конфигурацией; оптимизация; динамическое программирование; турбулентность; project; configuration; configuration management; optimization; dynamic programming; turbulence; environment